Biventricular longitudinal strain as a predictor of functional improvement after D-shant device implantation in patients with heart failure - Zhou, Yi; Li, He; Fang, Lingyun; Wu, Wenqian; Sun, Zhenxing; Zhang, Ziming; Liu, Manwei; Liu, Jie; He, Lin; Chen, Yihan; Xie, Yuji; Li, Yuman; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background The creation of an atrial shunt is a novel approach for the management of heart failure (HF), and there is a need for advanced methods for detection of cardiac function response to an interatrial shunt device. Ventricular longitudinal strain is a more sensitive marker of cardiac function than conventional echocardiographic parameters, but data on the value of longitudinal strain as a predictor of improvement in cardiac function after implantation of an interatrial shunt device are scarce. We aimed to investigate the exploratory efficacy of the D-Shant device for interatrial shunting in treating heart failure with reduced ejection fraction (HFrEF) and heart failure with preserved ejection fraction (HFpEF), and to explore the predictive value of biventricular longitudinal strain for functional improvement in such patients. Methods A total of 34 patients were enrolled (25 with HFrEF and 9 with HFpEF). All patients underwent conventional echocardiography and two-dimensional speckle tracking echocardiogram (2D-STE) at baseline and 6 months after implantation of a D-Shant device (WeiKe Medical Inc., WuHan, CN). Left ventricular global longitudinal strain (LVGLS) and right ventricular free wall longitudinal strain (RVFWLS) were evaluated by 2D-STE. Results The D-Shant device was successfully implanted in all cases without periprocedural mortality. At 6-month follow-up, an improvement in New York Heart Association (NYHA) functional class was observed in 20 of 28 patients with HF. Compared with baseline, patients with HFrEF showed significant reduced left atrial volume index (LAVI) and increased right atrial (RA) dimensions, as well as improved LVGLS and RVFWLS, at 6-month follow-up. Despite reduction in LAVI and increase in RA dimensions, improvements in biventricular longitudinal strain did not occur in HFpEF patients. Multivariate logistic regression demonstrated that LVGLS [odds ratio (OR): 5.930; 95% CI: 1.463–24.038; P = 0.013] and RVFWLS (OR: 4.852; 95% CI: 1.372–17.159; P = 0.014) were predictive of improvement in NYHA functional class after D-Shant device implantation. Conclusion Improvements in clinical and functional status are observed in patients with HF 6 months after implantation of a D-Shant device. Preoperative biventricular longitudinal strain is predictive of improvement in NYHA functional class and may be helpful to identify patients who will experience better outcomes following implantation of an interatrial shunt device.